Residual Effect of NPK Fertilizer towards Plant Growth and Corm Yield of Indonesian Konjac (Amorphophallus muelleri Blume) on Vertisol Soil - Singgih, Bambang; Soedarjo, Muchdar; Rusdi, Nurul; Ulinuhayani, Muhammad; Nurhidayat, Setia P. (Pusat Publikasi Nusantara, 2025)
Indonesian konjac (Amorphophallus muelleri Blume) naturally grows on forest under the shade of the trees. However, this crop has become an important commercial tuber crop due to the whay the tuber crops, Indonesian konjac has been cultivated by employing the relatively high input in cultural practices, especially the use of fertilizer. NPK fertilizer has been commonly used to cultivate Indonesian konjac to produce high yield of corm. The present study was undertaken to evaluate the residual effect of NPK fertilizer on growth and corm yield of Indonesian konjac. Vertisol soil previously unfertilized (A), previously fertilized with 100 kg NPK/ha (B) and previously fertilized with 200 kg NPK/ha (C) were used to grow Indonesian konjac. The Indonesian konjac grown on each soil (A, B or C) was fertilized with 0 kg NPK/ha, 150 kg NPK/ha and 300 kg NPK/ha. Thus, the study used 9 treatments, and each treatment was replicated three times. All data obtained were analyzed by employing the standard deviation from 3 replicates. The results of the present study revealed that NPK fertilizer addition did not increase plant height, shoot diameter, shoor dry weight, corm diameter, corm thickness and corm fresh weight of Indonesian konjac grown on Vertisol soil previously unfertilized, previously fertilized with 100 kg NPK/ha or previously fertilized with 200 kg NPK/ha. Thus, the results of the present study suggest that Vertisol soil is fertile and addition of NPK fertilizer is not necessary to grow this kind of konjac.